THE REPRESENTATIONS OF LIE ALGEBRAS ASSOCIATED TO LIE GROUPS - Husein, Hoor M (MAGISTRA, 2014)
The main aim in this study is to look for an interesting action with new properties from a Schureâs lemma that states that the action of the tensor product of Lie algebras representations which has interesting property. Our main work here is to give a representation of Lie algebra by intertwines these actions (representations) and to give a representation of Lie algebras associated to representation of Lie groups. Keywords: AC-Lie algebra, AC_Lie group, Tensor space, Hom space.